2022
DOI: 10.1111/jocn.16214
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of health‐promoting behaviours among pregnant women: A longitudinal study

Abstract: Aims and objectives:The aim of this study is to estimate differences in healthpromoting behaviour levels throughout the pregnancy trimesters, to identify distinct patterns of health-promoting behaviour trajectories during pregnancy and to evaluate predictors of these trajectory group memberships.Background: Promoting healthy lifestyle behaviours during pregnancy could decrease devastating outcomes for the mother and foetus. However, there is currently limited insight into the dynamics of health-promoting behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…A potential explanation for the lower levels of physical activity in women who use ART could be that they have significantly lower self‐efficacy compared to women who conceive naturally, as self‐efficacy was one of the predictors of physical activity in pregnant women who used ART in the present study. Higher levels of physical activity self‐efficacy were associated with more physical activity engagement (Yu et al, 2023). This correlation is supported by previous research (Cramp & Bray, 2009) and Bandura's theory, which posits that individuals with high self‐efficacy in physical activity are more willing to exert effort to overcome difficulties (Bandura, 1977).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential explanation for the lower levels of physical activity in women who use ART could be that they have significantly lower self‐efficacy compared to women who conceive naturally, as self‐efficacy was one of the predictors of physical activity in pregnant women who used ART in the present study. Higher levels of physical activity self‐efficacy were associated with more physical activity engagement (Yu et al, 2023). This correlation is supported by previous research (Cramp & Bray, 2009) and Bandura's theory, which posits that individuals with high self‐efficacy in physical activity are more willing to exert effort to overcome difficulties (Bandura, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…According to Green (1991), the minimum required sample size for multiple linear regression can be estimated using the formula n > 50 + 8 m , where m is the number of predictors. Based on the literature review, the predictors of physical activity were assumed to be self‐efficacy (Yu et al, 2023), knowledge (McKeough et al, 2022), social support (Grenier et al, 2021), age (Jones et al, 2021), education (Jones et al, 2021), occupation (Jones et al, 2021), monthly household income (Janakiraman et al, 2021), attendance at antenatal physical activity classes (Ahmadi et al, 2021), pre‐pregnancy physical activity habits (Janakiraman et al, 2021), and parity (Alaglan et al, 2020). Thus, in the present study, m is 10.…”
Section: Methodsmentioning
confidence: 99%
“…found positive correlations (p < 0.05) with measures of wellbeing and social support and negative correlation (p < 0.05) with depression.Einav et al [36] reported correlations between Relationship Satisfaction and Maternal Satisfaction that were statistically signi cant (i.e., p < .001) [31,34,35,37,40,. 69,70,73,75] provided no explicit measures of SOC, the majority of the prospective studies (n = 19; 38.8%) (see Table4) provided multiple measures of SOC[33,41,43, 46, 48,49,55,57, 60, 63, 64, 65, 66, 67, 68,71,74, 76, 78].…”
mentioning
confidence: 99%
“…Of these 18 studies, four studies [63, 64, 66, 69] indicated SOC measures in the 2nd trimester and two studies[60,75] speci ed SOC measures in the 3rd trimester. One study[31] completed questionnaires at 12, 24 and 36 weeks of gestation while one study[34] had responders completing the questionnaire at 39th week of gestation and 2 months postpartum. One study speci ed the 2nd and 3rd trimester as when the questionnaires were completed.…”
mentioning
confidence: 99%
See 1 more Smart Citation